Capacity and Readiness Assessment of Healthcare Facilities for Digital Health Interventions Against Tuberculosis and HIV in Addis Ababa, Ethiopia - Getachew, Emnet; Woldeamanuel, Yimtubezinash; Manyazewal, Tsegahun (Frontiers in Digital Health, 2022)
Background: There is a high level of concern that low-income countries lack the capacity and readiness to effectively adopt, implement, and scale up digital health interventions (DHIs). We aimed to assess the infrastructure and human resource capacity and readiness of healthcare facilities to adopt and implement any new DHI for tuberculosis (TB) and HIV care and treatment in Addis Ababa, Ethiopia. Method: We carried out a cross-sectional, mixed-methods study in 14 public healthcare facilities that provide TB and HIV care and treatment services. Providers' perceived readiness to adopt and implement digital health was assessed using a self-administered questionnaire designed based on an adapted eHealth readiness assessment model that covers six domains: core readiness, organizational cultural readiness, value proposition readiness, technological readiness, regulatory policy readiness, and operational resource readiness. The infrastructure and human resource capacity were assessed on-site using a tool adapted from the Technology Infrastructure Checklist. Internal consistency was assessed using Cronbach's alpha, and the significant relationship between the composite variables was assessed using Pearson's correlation coefficients (r). Result: We assessed 14 facilities on-site and surveyed 60 TB and HIV healthcare providers. According to Cronbach's alpha test, all the six technology acceptance domains had a value of greater than 0.8, suggesting a strong interrelatedness between the measuring items. The correlation between technological readiness and operational resource readiness was significant (r = 0.8). The providers perceived their work environment as good enough in electronic data protection, while more efforts are needed in planning, training, adapting, and implementing digital health. Of the 14 facilities, 64.3% lack the plan to establish a functional local area network, and 43% lack skilled staff on payroll to provide maintenance of computers and other digital technologies. Conclusion: Like many developing countries, there was a modest infrastructure and human resource capacity and readiness of public healthcare facilities in Addis Ababa, Ethiopia, to nurture and strengthen DHIs across the TB and HIV cascades of care. Technological and operational resource readiness, including funding and a well-trained workforce, are essential for successful implementation and use of digital health against the two infectious diseases of global importance in such settings.